Upaya Meningkatkan Konsentrasi Anak Usia Dini Dalam Menyimak Melalui Kegiatan Bercerita Menggunakan Metode Read Aloud Di TK Anggrek Loa Janan Kutai Kartanegara - Maharani Dwi Hartanti; Ujang Maulana Yusup (Jurnal Pendidikan Sosial Dan Konseling, 2025)
This study aims to improve the concentration of early childhood children in listening through storytelling activities using the Read Aloud method at Anggrek Loa Janan Kindergarten, Kutai Kartanegara. This classroom action research was conducted in two cycles with 17 children aged 5-6 years as subjects. Data were collected using observation sheets based on concentration indicators, including the ability to sit still, focus on listening, and actively respond during storytelling activities. The results showed an increase in children's concentration from 29% in the pre-cycle to 82% in the second cycle. This improvement was supported by the implementation of the Read Aloud method, which provides multisensory stimulation and social interaction in accordance with Vygotsky’s cognitive development theory. In conclusion, the Read Aloud method is effective in improving early childhood children's concentration in listening and is recommended as a consistent teaching strategy in early childhood education settings.